SOCIOCULTURAL CHARACTERISTICS OF SCIENTIFIC TRUST AND BELIEF: AN EPISTEMOLOGICAL INTERPRETATION (World Bulletin of Social Sciences, 2023)
The article reveals the current meaning of the philosophical categories “Faith”, “Unbelief”, “Beliefs”, their philosophical and socio-cultural conditionality. In addition, methods of actualization and transmission, as well as changeability of culture, are shown. At the same time, the dialectics of cultural production, the relationship of faith, disbelief, and belief are explored